Will Greenland be the last refuge for the continental European small-white orchid?Niche modeling of future distribution of Pseudorchis albida - Kolanowska, Marta; Nowak, Sławomir; Rewicz, Agnieszka (Frontiers in Environmental Science, 2022)
Climate change affect populations of plants, animals and fungi not only by direct modifications of their climatic niches, but also by altering their ecological interactions. In this study the future distribution of suitable habitats for the small-white orchid (Pseudorchis albida) was predicted using ecological niche modelling. In addition, the effect of global warming on the spatial distribution and availability of the pollen vectors of this species was evaluated. Due to the inconsistency in the taxonomic concepts of Pseudorchis albida the differences in the climatic preferences of three proposed subspecies were investigated. Due to the overlap of both morphological and ecological characters of ssp. albida and ssp. tricuspis they are considered to be synonyms and the final analyses were done using ssp. albida s.l. and ssp. straminea. All of the models predict that with global warming the number of suitable niches for these orchids will increase. This significant increase in preferred habitats is expected to occur in Greenland, but habitat loss in continental Europe will be severe. Within continental Europe Pseudorchis albida ssp. albida will lose 44-98% of its suitable niches and P. albida ssp. straminea will lose 45-90% of its currently available habitats. An opposite effect of global warming is predicted for pollinators of P. albida s.l. and almost all insects studied will be subject to habitat loss. Still, within the predicted potential geographical ranges of the orchid studied some pollen vectors are expected to occur and these can support the long-term survival of the small-white orchid.